2020
DOI: 10.1111/coep.12461
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Community Deterrence: Evidence From the National Hockey League

Abstract: Community and specialized enforcement are recognized as important components of deterring antisocial behavior. To provide insights on the interplay between deterrence methods, we examine the empirical evolution of fighting and scoring in the National Hockey League using time series data. We identify structural changes that correlate with changes in player behavior and rules. In particular, we find that player behavior related to fighting changed 4 or 5 years prior to most rule changes aimed at reducing fightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…These results are consistent with Depken, Groothuis, and Strazicich [ 10 ], who find that changes in fighting behavior in the NHL over the past half-century were largely the result of changing norms within the sport, rather than league rule changes. Their study examines data from 1957 through 2013, roughly the beginning of the sample period in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with Depken, Groothuis, and Strazicich [ 10 ], who find that changes in fighting behavior in the NHL over the past half-century were largely the result of changing norms within the sport, rather than league rule changes. Their study examines data from 1957 through 2013, roughly the beginning of the sample period in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have examined a range of questions relevant to coaches and general managers, such as whether fighting affords teams a tactical advantage and is related to better game outcomes [ 6 ]. Others have explored league and ownership incentives to maintain support for fighting in the face of increasing understanding about the impact of head injuries [ 7 9 ], incentives for individual players to fight more [ 6 ], the conditions under which fights are more likely to occur [ 7 , 10 ], and ethics of fighting [ 11 ]. DeAngelo, Humphries, and Reimers [ 12 ] use data from an earlier era in the NHL to examine the effect of fights and officiating on body checking.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2004 article, Depken and Wilson found that the addition of a second referee during the 1998 and 1999 NHL seasons, coincided with a reduction in fighting and increase in scoring. They also found that television viewership increased while in-arena attendance did not change during this time (Depken and Wilson, 2004;Depken et al, 2020). Following the 2004-2005 NHL lockout, several rules were implemented to reduce violence and increase goal scoring.…”
Section: Discussionmentioning
confidence: 99%
“…Head injuries are common among NHL players, and approximately 9% of all concussions result from fighting (Donaldson et al, 2013 ; Hutchison, 2015 ). Concussions contribute significantly to games missed and account for salary loss of $42.8 million annually (Depken et al, 2020 ). There is growing awareness surrounding the sequelae of head trauma and concussions in athletes (McKee et al, 2013 ; Kuhn and Solomon, 2015 ; Smith et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation